Loeys–Dietz syndrome with aortic wall necrosis secondary to external wrapping. (25th December 2017) - Yamamoto, Masaki; Iguchi, Mitsuko; Yamamoto, Masaki; Hiroi, Makoto
Abstract: External aortic wrapping may overcompress the aortic wall. An 18-year-old man underwent valve-sparing aortic root replacement for annuloaortic ectasia caused by Loeys–Dietz syndrome. External Dacron graft wrapping was performed to protect the ascending aorta. A year later, he underwent mitral valve repair. Intraoperatively, after unwrapping the external graft, the wrapped ascending aortic wall appeared necrotic. Histopathology showed damaged smooth muscle cells in the adventitia and outer media with unaffected inner layers and an intact intimal surface. Ischaemic necrosis of the aortic wall was associated with arterial insufficiency secondary to overcompression of the aortic wall that was already weakened by Loeys–Dietz syndrome. We describe a patient with Loeys–Dietz syndrome in whom pathognomonic necrosis in the wrapped aortic wall was observed histopathologically.